Teacher training for Inclusive Classroom: A Road Map - Sarwer, Ghulam (IJRDO- Journal of Educational Research, 2016)
This paper presents the current status of teacher education for inclusive education, i.e.preparation of teachers for inclusive classroom as well as the need for introducing changes in theinclusive education curricula, leading towards a more efficient development of competences forworking with all students. It is found that the inclusive education curricula do not contribute tothe development of competences and preparation of teachers for inclusive classroom. The basicobstacles in preparation of teacher for inclusive education include inadequate curricula,dysfunctional professional practices and negative attitude of educators towards inclusiveeducation. The concluding part of this paper points out that the key factors for changes ininclusive education comprise sufficient motivation of educators, awareness about theresponsibility of the faculty to teach in accordance with the inclusive education concept, as wellas the support to these faculties through wide social action. The implications for enhancement oftraining programme for teachers include introducing changes into study programmes andimplementing the strategies in practice, leading towards more effective preparation of teachersfor inclusive classroom